2009
DOI: 10.1038/sj.bjc.6604896
|View full text |Cite
|
Sign up to set email alerts
|

Increased tumour dihydroceramide production after Photofrin-PDT alone and improved tumour response after the combination with the ceramide analogue LCL29. Evidence from mouse squamous cell carcinomas

Abstract: Photodynamic therapy (PDT) has been proven effective for treatment of several types of cancer. Photodynamic therapy alone, however, attains limited cures with some tumours and there is need for its improved efficacy in such cases. Sphingolipid (SL) analogues can promote tumour response in combination with anticancer drugs. In this study, we used mouse SCCVII squamous cell carcinoma tumours to determine the impact of Photofrin-PDT on the in vivo SL profile and the effect of LCL29, a C6-pyridinium ceramide, on P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
29
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 35 publications
6
29
0
Order By: Relevance
“…1B relative to the de novo ceramide pathway. Others (2025) and we (19,2630) have shown the involvement of the de novo ceramide pathway in response to anticancer therapeutics, including PDT, in vitro and in vivo . Foscan, a photosensitizer more potent than Photofrin (31), and clinically proven effective for PDT of head and neck cancers (32), was chosen for these investigations.…”
Section: Introductionmentioning
confidence: 86%
See 1 more Smart Citation
“…1B relative to the de novo ceramide pathway. Others (2025) and we (19,2630) have shown the involvement of the de novo ceramide pathway in response to anticancer therapeutics, including PDT, in vitro and in vivo . Foscan, a photosensitizer more potent than Photofrin (31), and clinically proven effective for PDT of head and neck cancers (32), was chosen for these investigations.…”
Section: Introductionmentioning
confidence: 86%
“…Using LCL29 (11,18), in combination with Photofrin-PDT, we have shown moderately improved in vivo response of mouse SCCVII squamous carcinomas (19). However, the long-term effect of the combination PDT + LCL29 is unknown.…”
Section: Introductionmentioning
confidence: 97%
“…Moreover, SMase activation enhanced the killing effects of ionizing radiation in vitro and in vivo [90], and increasing endogenous ceramide levels in radioresistant HNSCC cell lines induced apoptosis by restoring the death signal transduction pathway, which had been ineffective following irradiation owing to a lack of ceramide generation [91]. Recently, it was demonstrated that ceramide analog LCL29 enhanced tumor response to photofrin-photodynamic therapy [92].…”
Section: Head and Neck Cancermentioning
confidence: 99%
“…They had some inhibition at higher concentrations, supporting the fact that both agents may act indirectly on the enzyme (unpublished observations). Additionally, photodynamic therapy (Separovic et al, 2009), -tocopherol , and XM462 (Munoz-Olaya et al, 2008) may function as indirect inhibitors of dihydroceramide desaturase by modulating the redox status of the cells as in case of hydrogen peroxide.…”
Section: Two Major Metabolites Of 4-hpr Have Been Identified: N-(4-mementioning
confidence: 99%